The Effect of Shionone on Sepsis-Induced Acute Lung Injury by the ECM1/STAT5/NF-κB Pathway - Song, Yi; Wu, Qian; Jiang, Huojun; Hu, Aihao; Xu, Lingqi; Tan, Caiping; Zhang, Biao; Yu, Rongming; Qiu, Yizhen; Wang, Xin; Yang, Wenzhong (Frontiers in Pharmacology, 2022)
Purpose: The purpose of the present study was to estimate the effect of shionone (SHI) on sepsis-induced acute lung injury (ALI). Methods: The cecal ligation and puncture (CLP) surgery was performed to induce sepsis in mice. Pulmonary hematoxylin and eosin staining, the wet/dry ratio, myeloperoxidase (MPO) activity, and the survival rate were detected. The RAW264.7 cells were treated with SHI and stimulated with lipopolysaccharide (LPS). The cells were also overexpressed by extracellular mechanism protein 1 (ECM1) adenovirus. The relative levels of granulocyte–macrophage colony-stimulating factor, IL-6, IL-1β, TNF-α, IL-10, and TGF-β in the serum and supernatant were measured by ELISA. The protein expressions of ECM1, p-STAT5, signal transducer and activator of transcription 5 (STAT5), p-NF-κB, nuclear factor kappa-B (NF-κB), Arg1, CD206, CD16/32, and iNOS in the CLP-induced lung tissues and LPS-induced cells were detected by western blot. The cell counts of Ly6G, F4/80, CD16/32, and CD206 were evaluated by flow cytometry. The ECM1 expression was also observed by immunohistochemistry and immunofluorescence staining. Results: As a result, the histopathological change, pulmonary edema, and the MPO activity were relieved by SHI. SHI treatment increased the percentage of neutrophil and macrophage in the bronchoalveolar lavage fluid. Besides, SHI administration inhibited pro-inflammatory cytokines and M1 phenotype indices, as well as augmented the anti-inflammatory cytokines and M2 phenotype indices. SHI also attenuated the ECM1/STAT5/NF-κB pathway both in vivo and in vitro. The overexpression of ECM1 confirmed that the regulated effect of SHI was due to ECM1 signaling. Conclusion: In conclusion, the present study suggests that SHI ameliorated sepsis-induced ALI by screwing M1 phenotype to M2 phenotype macrophage via the ECM1/STAT5/NF-κB pathway.